Differential Effects of Anthracycline-based Neoadjuvant Chemotherapy on Stromal and Intratumoral FOXP3+ Tumor-Infiltrating Lymphocytes in Invasive Breast Cancer of No Special Type - Rustamadji, Primariadewi; Wiyarta, Elvan; Pramono, Meike; Maulanisa, Sinta Chaira (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Neoadjuvant chemotherapy (NAC) plays a crucial role in the management of invasive breast cancer with no special type (IBC-NST), with the immune system's response to cancer heavily relying on the dynamics between tumor-infiltrating lymphocytes (TILs) and cancer cells. In this study, the differential effects of anthracycline-based NAC on stromal and intratumoral foxhead box P3 (FOXP3+) TILs expressions were specifically examined.METHODS: In this cross-sectional study, 32 IBC-NST samples were evaluated for pre- and post-NAC FOXP3+ TIL expression as well as the changes of FOXP3+ TIL expression. Comprehensive data collection regarding subjects' age, tumor size, grade, lymphovascular invasion, regional lymph node metastasis, and receptor status were conducted. Immunohistochemistry was utilized to quantify FOXP3+ TILs. The stromal, intratumoral and total FOXP3+ TILs expression were then analyzed.RESULTS: Significant reductions in FOXP3+ TIL expression post-NAC were observed, with stromal FOXP3+ TILs showing a median decrease of 3.6 units in subjetcs aged ≥50 years (p=0.013) and a median decrease of 13.2 units in subjects with tumors ≥5 cm after NAC (p=0.006). In contrast, intratumoral FOXP3+ TILs remained relatively stable, with minor changes. The total FOXP3+ TIL expression, combining stromal and intratumoral components, was significantly decreased with a median of 13.0 units decreased to 5.3 units (p<0.001).CONCLUSION: This study highlights the significant reduction in stromal FOXP3+ TIL expression after NAC treatment in IBC-NST subjects, in contrast to the relatively stable intratumoral FOXP3+ TILs. Understanding these differences may guide future therapeutic strategies and improve treatment outcomes for IBC-NST.KEYWORDS: biomarkers, chemotherapy, FOXP3, prognostic, response, lymphocyte